ON THE RESULTS OF CATEGORY IN TOPOLOGICAL GROUPOID - Mohammed Thamir Ibraheem; Taghreed Hur Majeed (مجلة كلية التربية, 2022)
This search discuss the problem between topological group and topological groupoid . We shall take some consequences of groupoid space and group space and make a relation with the tensor product , As well we discuss the action between the action of topological groupoid and the action of topological group and we attach a relation with the tensor product . Some remarks , proposition and examples are our own except if else is referred to.